Statics and mechanics of materials - Hibbeler, R. C. (Pearson Education Limited, 2019)
For courses in introductory combined Statics and Mechanics of Materials courses found in ME, CE, AE, and Engineering Mechanics departments. Statics and Mechanics of Materials represents a combined abridged version of two of the author's books, namely Engineering Mechanics: Statics, Fourteenth Edition and Mechanics of Materials, Tenth Edition with Statics and Mechanics of Materials represents a combined abridged